2011
DOI: 10.1007/s11250-011-9833-1
|View full text |Cite
|
Sign up to set email alerts
|

Serological and molecular detection of Mycobacterium avium subsp. paratuberculosis in cattle of dairy herds in Colombia

Abstract: The objective of this study is the detection of Mycobacterium avium subsp. paratuberculosis (MAP) by serum enzyme-linked immunosorbent assay (ELISA), fecal polymerase chain reaction (PCR), and fecal culture in Colombian dairy herds. Serum and fecal samples from asymptomatic cows (n = 307) of 14 dairy herds were tested for MAP by an unabsorbed ELISA test (ELISA-A). Serum and fecal samples from positive ELISA-A animals (n = 31) were further tested by an absorbed ELISA test (ELISA-B) and PCR. Fecal samples from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
1
19
0
1
Order By: Relevance
“…Los casos compatibles con paratuberculosis se presentaron siempre de manera individual y esporádica a lo largo del tiempo. Varios estudios diagnósticos realizados a diferentes animales en ese hato entre 2000 y 2010, han proporcionado resultados que indican la presencia de MAP en el rebaño (16)(17)(18). A pesar del seguimiento de los casos compatibles y los exámenes realizados a los animales del hato, los resultados de diagnóstico clínico e histopatológico obtenidos durante el periodo de tiempo 2000-2008 no se habían analizado sistemáticamente hasta la fecha.…”
Section: Introductionunclassified
“…Los casos compatibles con paratuberculosis se presentaron siempre de manera individual y esporádica a lo largo del tiempo. Varios estudios diagnósticos realizados a diferentes animales en ese hato entre 2000 y 2010, han proporcionado resultados que indican la presencia de MAP en el rebaño (16)(17)(18). A pesar del seguimiento de los casos compatibles y los exámenes realizados a los animales del hato, los resultados de diagnóstico clínico e histopatológico obtenidos durante el periodo de tiempo 2000-2008 no se habían analizado sistemáticamente hasta la fecha.…”
Section: Introductionunclassified
“…Positivity was detected in 89 (4.6%) of 1950 serum samples (6) and in 424 (12.4%) of 10,280 samples in cattle (21), while 3.48% of 3961 cattle over 2 years of age were found to be positive in terms of seroprevalence in Poland (22). In Colombia, Fernandez-Silva et al (23) determined positivity at a rate of 10.1%, while in Turkey, Makav and Gokce (24) found a 3.5% prevalence rate for subclinical paratuberculosis in the Kars region, and in Burdur Province a rate of 6.2% was reported by Ozturk et al (25). In the present study, in Kayseri Province, 12.24% and 10.88% of 147 blood samples taken from paratuberculosis-suspected animals were detected as positive and suspicious by ELISA, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…It is necessary to define the exact status of the disease through well-designed prevalence/incidence studies, considering that no whole national data is available. In this regard, just some local estimates are currently available (Patiño and Estrada, 1999;Ramírez et al, 2001;Fernández et al, 2011a;2011b;Benavides et al, 2016;Correa et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Only one previous study reported molecular characterization of strains isolated in Colombia (Fernández et al, 2011b), being this insufficient to consider the definition of "indigenous strains" and the ulterior design of vaccines. It would be necessary to conduct studies on wider regions, considering infectionassessment on cattle and other-than-cattle susceptible populations (even local wildlife) to generate prophylactic strategies according to Colombian MAP molecular and epidemiological diversity.…”
Section: Paratuberculosis In Colombiamentioning
confidence: 99%